Cesarean birth and maternal morbidity among Black women and White women after implementation of a blended payment policy. (16th July 2020) - Snowden, Jonathan M.; Osmundson, Sarah S.; Kaufman, Menolly; Blauer Peterson, Cori; Kozhimannil, Katy Backes
Abstract: Objective: To test whether Minnesota's blended payment policy had differential effects on cesarean use and maternal morbidity among black women and white women in Minnesota, as compared to six control states. Data sources/study setting: Claims data from births to Medicaid fee‐for‐service beneficiaries, 2006‐2012, in Minnesota (policy state) and six control states (Wisconsin, Iowa, Illinois, Oregon, Idaho, and Montana). Study design: The key study intervention was Minnesota's blended payment policy, which established one single payment rate for uncomplicated vaginal and cesarean births in 2009. The primary outcome was cesarean birth, and secondary outcomes were maternal morbidity (composite), postpartum hemorrhage, and chorioamnionitis. Policy effects were assessed using race‐stratified comparative interrupted time series analysis. Principal findings: Following policy implementation, cesarean use decreased among both black and white women in Minnesota compared to control states; this decline was larger among black women (−2.88 percent 3‐year cumulative decline, from a prepolicy cesarean rate of 22.2 percent) than among white women (−1.32 percent, P = .0013). Postpartum hemorrhage increased, with larger increases among black women (1.20 percent 3‐year cumulative increase), compared with white women (0.48 percent, P < .001) in Minnesota compared with control states. Conclusions: Policy‐related declines in cesarean use after Minnesota's blended payment policy were larger in black women. Increases in postpartum hemorrhage signal potential unintended consequences of policy‐related cesarean reduction.